2019
DOI: 10.1155/2019/9736047
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Intraocular Pressure Causes Abnormal Reactivity of Mouse Retinal Arterioles

Abstract: Objective. Glaucoma is a leading cause of severe visual impairment and blindness. Although high intraocular pressure (IOP) is an established risk factor for the disease, the role of abnormal ocular vessel function in the pathophysiology of glaucoma gains more and more attention. We tested the hypothesis that elevated intraocular pressure (IOP) causes vascular dysfunction in the retina. Methods. High IOP was induced in one group of mice by unilateral cauterization of three episcleral veins. The other group rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 66 publications
1
51
0
2
Order By: Relevance
“…In the study, elevated IOP blunts retinal arteriole reactivity in response to the endothelium-dependent vasodilator acetylcholine, but not to the endothelium-independent nitric oxide donor, nitroprusside. Also, retinal arteriole responses to changes in perfusion pressure are compromised in eyes with elevated pressure, suggesting that autoregulation is impaired (Gericke et al, 2019). In the DBA/2J mouse model of inherited glaucoma, several molecular changes in the ONH are detectable before damage to optic nerve axons have been elucidated, and these include endothelin induction in microglia (Howell et al, 2011).…”
Section: Blood Flow Regulation Is Impaired In Glaucomamentioning
confidence: 99%
“…In the study, elevated IOP blunts retinal arteriole reactivity in response to the endothelium-dependent vasodilator acetylcholine, but not to the endothelium-independent nitric oxide donor, nitroprusside. Also, retinal arteriole responses to changes in perfusion pressure are compromised in eyes with elevated pressure, suggesting that autoregulation is impaired (Gericke et al, 2019). In the DBA/2J mouse model of inherited glaucoma, several molecular changes in the ONH are detectable before damage to optic nerve axons have been elucidated, and these include endothelin induction in microglia (Howell et al, 2011).…”
Section: Blood Flow Regulation Is Impaired In Glaucomamentioning
confidence: 99%
“…One of the main risk factors for glaucoma is elevated intraocular pressure (IOP). Intriguingly, moderately elevated IOP was shown to induce excessive ROS levels, increased NOX2 expression, and endothelial dysfunction in retinal arterioles of mice, suggesting that IOP elevation compromises vascular function in the retina [ 159 ]. However, there are also other pathogenic mechanisms related to glaucoma, such as inflammation activated by ROS and glutamate excitotoxicity [ 160 ], which are not necessarily related to elevated IOP levels [ 156 ].…”
Section: Ros and Glaucomamentioning
confidence: 99%
“…62 It has been suggested that these changes may reflect a response to reduced metabolic demand following RGC death or that degenerative processes may impair blood vessel regulation through production of vasoconstrictive substances such as reactive oxygen species or endothelin. 37 , 63 , 64 …”
Section: Discussionmentioning
confidence: 99%